TEKNOLOGI PROCESS AWARE INFORMATION SYSTEM (PAIS) MANAJEMEN EKSTRAKURIKULER UNTUK OTOMASI PEMANTAUAN KEGIATAN - Munna, Daurin Nabilatul; Prasetyo, Gigih Agung; Maghfira, Aulia Ilmi; Yaqin, Muhammad Ainul (SKANIKA: Sistem Komputer dan Teknik Informatika, 2024)
Education in Indonesia, including in Malang City, has seen rapid development in recent decades. Extracurricular activities, as an integral part of education, offer students opportunities to develop skills, talents, and interests beyond the main curriculum. However, the current management of extracurricular activities is still manual and inefficient. To address this issue, we propose the implementation of a Process-Aware Information System (PAIS) to automate the monitoring of extracurricular activities. This system involves input such as school data, student data, and extracurricular data. The outputs include reports on extracurricular activities, student talents and interests, and school achievements. The process includes student registration for extracurricular activities, validation by administrators, activity scheduling, attendance monitoring, and reporting. This system is expected to efficiently and accurately monitor these activities. Through the PAIS workflow, we ensure more efficient and real-time management and monitoring of extracurricular activities. This system assists in improving extracurricular management, data accuracy, better decision-making, and time savings.